JAK inhibition induces silencing of T Helper cytokine secretion and a profound reduction in T regulatory cells. (15th June 2015) - Keohane, Clodagh; Kordasti, Shahram; Seidl, Thomas; Perez Abellan, Pilar; Thomas, Nicholas S. B.; Harrison, Claire N.; McLornan, Donal P.; Mufti, Ghulam J.
Summary CD4+ T cells maintain cancer surveillance and immune tolerance. Chronic inflammation has been proposed as a driver of clonal evolution in myeloproliferative neoplasms (MPN), suggesting that T cells play an important role in their pathogenesis. Treatment with JAK inhibitors (JAKi) results in improvements in MPN‐associated constitutional symptoms as well as reductions in splenomegaly. However, effects of JAKi on T cells in MPN are not well established and the baseline immune signature remains unclear. We investigated the frequency and function of CD4+ T cell subsets in 50 MPN patients at baseline as well as during treatment with either ruxolitinib or fedratinib in a subset. We show that CD4+ CD127low CD25high FOXP3+ T regulatory cells are reduced in MPN patients compared to healthy controls and that this decrease is even more pronounced following JAKi therapy. Moreover, we show that after 6 months of treatment the number of T helper (Th)‐17 cells increased. We also describe a functional 'silencing' of T helper cells both in vivo and in vitro and a blockade of pro‐inflammatory cytokines from these cells. This profound effect of JAKi on T cell function may underlay augmented rates of atypical infections that have been reported with use of these drugs.